Mutation Breeding in Coffee with Special Reference to Leaf Rust Protocols - Ingelbrecht, Ivan L.W; Silva, Maria do Céu Lavado da; Jankowicz-Cieslak, Joanna (Springer Nature, 2023)
This open-access book provides a comprehensive overview of current methodologies for improving resistance to leaf rust in coffee, one of the world's most important cash crops and beverages. Coffea arabica L. (Arabica) accounts for about 60% of the world's coffee production. Coffee leaf rust (CLR), caused by the fungus Hemileia vastatrix is the major disease affecting Arabica coffee resulting in losses of over $1 billion annually. The geographical distribution of CLR is expanding due to climate change. Moreover, the genetic improvement of Arabica coffee is constrained due to its very narrow genetic base. This protocol book introduces essential concepts of mutation breeding as an efficient tool to increase the genetic diversity of Arabica coffee and presents practical methods on mutation induction and screening for resistance to CLR. Current breeding approaches, challenges and opportunities for Arabica coffee improvement are briefly reviewed and a survey of common coffee diseases with emphasis on CLR is presented. Practical protocols for mutation induction and screening for resistance to CLR are described, including novel methods for single-cell mutagenesis using in vitro cell and tissue culture techniques and for genome-wide screening of induced mutations using genomics tools. Each protocol chapter has an introduction and is supported by example results. Given the impact of recent CLR epidemics on Arabica coffee production in Latin America, the book is intended to serve as a timely reference and guide for students and researchers in the agricultural sciences, plant pathologists and breeders, as well as growers and end-users interested in producing novel coffee genotypes for genetic studies, breeding, and commercial applications.